A remarkable new species of Hippeastrum (Amaryllidaceae) from the Serra da Mantiqueira, Southeastern Brazil - Campos-Rocha, Antonio; Da Silva Medeiros, Alexandre; Meerow, Alan William; Andre Sanz-Veiga, Priscila; Koch, Ingrid; Dutilh, Julie Henriette Antoinette (Phytotaxa, 2022)
Serra da Mantiqueira is the most important mountain range in eastern South America, known for its high levels of species richness and endemism. A new species of Amaryllidaceae endemic to the region was recently identified, described and illustrated herein. It can be recognized by its rupicolous habit, large bulbs, reaching 12 cm in diameter, annual, lorate leaves, white flowers with pink striations and perigonal tube up to 1.5 cm long. Comments on its habitat, conservation status, phenology data, photographs and illustrations are provided, as well as comparison with the most morphologically similar species. Known by only a single population, exposed to several types of threats and with limited guarantee of protection, Hippeastrum abatinguara is considered Critically Endangered. Additionally, a key to the species of Hippeastrum occurring in the Serra da Mantiqueira is presented, accompanied by photographs of these species in their natural habitats.